Health and Safety Culture as a Competitive Advantage for Knowledge‐based Organizations: An HSEC Model Perspective. (20th March 2017) - Firoozi, Naser Hassanzadeh; Hatami, Akram
Abstract : Because knowledge is increasingly considered to be a key resource for companies, organizations must create and foster knowledge‐sharing culture. A clear plan and strategy for knowledge creating, sharing it, and managing it provides sustainable competitive advantages for knowledge‐based organizations. Knowledge as an important source of capital for an organization can only be created and managed properly and successfully in a healthy cultural environment. The knowledge stores of organizations are in the minds of their employees, and it is through the art of management that a climate and policy for converting this tacit and valuable knowledge into explicit knowledge is created. This study employs the health, safety, environment, and culture (HSEC) model as a managerial tool to help managers create a health and safety culture for creating and managing knowledge and also gain a real competitive advantage in this highly competitive era. According to this model, knowledge‐based organizations must consider the role of cultural assessment, control risk, cultural hazards, and cultural syndromes when creating a health and safety culture. A successful HSEC model enables an organization to manage its complexity and uncertainty, improve performance, create competitive advantages, and enhance its business reputation. This model will create a deep understanding of a health and safety culture that facilitates the interaction and conversion process and also determines how the knowledge process should be developed and managed by identifying cultural hazards and risks. Copyright © 2017 John Wiley & Sons, Ltd.